2011
DOI: 10.1007/s00227-011-1799-z
|View full text |Cite
|
Sign up to set email alerts
|

Time and space: genetic structure of the cohorts of the common sea urchin Paracentrotus lividus in Western Mediterranean

Abstract: Spatio-temporal variability in settlement and recruitment, high mortality during the first life-history stages, and selection may determine the genetic structure of cohorts of longlived marine invertebrates at small scales. We conducted a spatial and temporal analysis of the common Mediterranean sea urchin Paracentrotus lividus to determine the genetic structure of cohorts at different scales. In Tossa de Mar (NW Mediterranean), recruitment was followed over 5 consecutive springs (2006-2010). In spring 2008, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
37
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 62 publications
3
37
0
Order By: Relevance
“…; Calderón et al . ). However, to our knowledge, these findings represent the first documented case of environmentally driven adaptive morphological differentiation proceeding under conditions of chaotic genetic patchiness.…”
Section: Discussionmentioning
confidence: 97%
“…; Calderón et al . ). However, to our knowledge, these findings represent the first documented case of environmentally driven adaptive morphological differentiation proceeding under conditions of chaotic genetic patchiness.…”
Section: Discussionmentioning
confidence: 97%
“…Previous studies assessing the population structure of P. lividus using different sets of mitochondrial and nuclear DNA markers found significant genetic differentiation only across two known oceanic discontinuities, the Almería‐Oran front separating the Atlantic and the Mediterranean populations (Calderón, Giribet, & Turon, ; Duran, Palacín, Becerro, Turon, & Giribet, ), and the Adriatic‐Ionian front (Maltagliati, Giuseppe, Barbieri, Castelli, & Dini, ). Temporal variability among different cohorts of the same localities was also assessed suggesting little temporal variation, with some exceptions associated with abnormalities of circulation patterns (Calderón, Palacín, Palacín, & Turon, ; Calderón, Pita, Brusciotti, Palacín, & Turon, ) or chaotic genetic patchiness (Couvray & Coupé, ). However, it has been suggested that P. lividus might present higher levels of structuring across the Atlantic and Mediterranean than previously suggested (Penant, Aurelle, Feral, & Chenuil, ).…”
Section: Introductionmentioning
confidence: 99%
“…In those studies that resampled, some populations are temporally stable Lambert et al2003;Kovach et al 2010), while the genetic signature of other populations change (Smolenski et al 1993;Purcell et al 1996;Cook et al 2007;Larsson et al 2010;Horne et al 2012). Populations that undergo detectable change are generally a minority among temporally stable populations across a species range (Cook et al 2007;Calderon et al 2012). The present study aims to examine the phylogeographic structure of Paracalanus quasimodo and Temora turbinata combined with temporal sampling to determine the stability of populations within a site and of the relationships between sites.…”
Section: Introductionmentioning
confidence: 99%
“…More temporal sampling in phylogeographic studies is needed in order to evaluate the degree of short-term variability within populations (Horne et al 2012), as most studies to date are limited in the numbers of temporal samples (Purcell et al 1996;Lambert et al 2003;Cook et al 2007;Horne et al 2012), or the numbers of sites sampled (Smolenski et al 1993;Calderon et al 2012). Purcell (1996) demonstrates how populations of the same species undergo different pressures resulting in varied changes in genetic identity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation